Pengaruh Pengaruh Media Audiovisual Terhadap Keterampilan Dribbling dan Shooting Bola Basket: - - Mohamad Yusuf Arifin; Hilmy Aliriad; Benny Widya Priadana (Universitas Hamzanwadi, 2026)
The problem of this study is the low basic dribbling and shooting skills of ninth-grade students at SMP Negeri 2 Montong, which is thought to be caused by the lack of variety and appeal in conventional teaching methods. The purpose of this study is to evaluate the effectiveness of using audiovisual media in improving dribbling and shooting skills in basketball. The method used is a quasi-experiment with a single-group pretest-posttest design. The research sample consisted of 26 students selected using purposive sampling. The research instrument was a dribbling and shooting skills test with a validated assessment rubric. The data were analyzed using the Paired Sample t-Test statistical test with the help of SPSS software. The results showed a significant increase in the average score from 59.68 on the pretest to 78.92 on the posttest. The t-test results showed a very significant difference (t = -28.151; p = 0.000). The conclusion of this study is that the use of audiovisual media is proven to be effective and has a significant positive impact on improving dribbling and shooting skills in basketball among students. Therefore, it is recommended that audiovisual media be integrated as an innovative learning method in physical education, especially for mastering the basic techniques of basketball.